Indian Ocean Dipole intensifies Benguela Niño through Congo River discharge - Michael J. McPhaden; Sreelekha Jarugula; Léo C. Aroucha; Joke F. Lübbecke (Communications Earth & Environment)
Abstract Benguela Niños are episodes of unusual El Niño-like warming in the upwelling zone off the coast of southwest Africa, with consequential impacts on marine ecosystems, coastal fisheries and regional weather. The strongest Benguela Niño in the past 40 years occurred in February–April 1995 with local sea surface temperature anomalies up to 4 °C off the coast of Angola and Namibia. Here, we show that a strong Indian Ocean Dipole in September–November 1994 helped boost the amplitude of the 1995 Benguela Niño through a land bridge involving Congo River discharge. We use atmospheric, oceanic, and hydrological data to demonstrate the sequential linkage between Indian Ocean Dipole development, unusually high rainfall in the Congo River basin, high Congo River discharge, low salinity near the Congo River mouth, and southward advection of this low salinity water into the Benguela upwelling region. The low salinity water isolated the surface mixed layer from the thermocline, which limited vertical mixing with colder subsurface waters and led to enhanced sea surface temperature warming. We also discuss how other Indian Ocean Dipole events may have similarly affected subsequent Benguela Niños and the possibility that Indian Ocean Dipole impacts on Benguela Niños may become more prominent in the future.